Misi Umat Pasionis Sebagai Sarana Katekese (Tinjauan Katekese Dalam Pemikiran Beverly) - Damianus, Kristianus; Firmanto, Antonius Denny (Sekolah Tinggi Pastoral IPI Malang, 2021)
English: This article focuses on the Mission of the Passionist as a Tool of Catechesis (Beverly Thought Catechesis Overview). I am interested and have anxieties discussing articles about the mission of the Passionists as a means of catechesis for the faith of Catholics in West Kalimantan for several reasons. First, Catholics in the interior need a refreshing faith. Second, through the mission of the Passionists, the people are invited to be closer to the crucified Christ and at the same time live the suffering of Jesus. Third, the people need enlightenment of faith on the part of the Church as a hierarchy. Finally, through this article I would like to introduce you to the spirituality and charism of the Passionist Congregation today. The method I use in writing this article is through personal interviews and literature. After going through interviews and obtaining data through literature then analyzed and combined. Thus, the results from the field and the results from the literature found a suitable thought between Beverly's thinking and the implementation of the Mission of the Passionists. The results of the ideas of Beverly and the Mission of the Passionists are a means of evaluating and seeing this mission in a comprehensive and holistic manner. Therefore, passionist spirituality continually renews itself with knowledge, research, and research on a mission or mission. The mission of the Passionists is to be a fine axis and torch in the witness of the proclamation of the mission of the Church in the world. This mission does not stop at the completion of the program but continues and is lived out by the faithful. Bahasa Indonesia: Artikel ini memiliki fokus pada Misi Umat Pasionis sebagai Sarana Katekese (Tinjauan Katekese Pemikiran Beverly). Saya tertarik dan memiliki kegelisahan membahas artikel tentang misi umat pasionis sebagai sarana katekese iman umat Katolik di Kalimantan barat karena beberapa alasan. Pertama, umat Katolik di pedalaman membutuhkan penyegaran iman. Kedua, melalui misi Umat Pasionis ini umat diajak untuk semakin dekat dengan Kristus tersalib sekaligus menghayati penderitaan Yesus. Ketiga, umat membutuhkan pencerahan iman dari pihak Gereja sebagai hirarki. Terakhir bahwa melalui artikel ini saya hendak mengenalkan spiritualitas dan kharisma Kongregasi Pasionis di masa sekarang ini. Metode yang penulis gunakan dalam penulisan artikel ini ialah melalui wawancara personal dan kepustakaan. Setelah melalui wawancara dan memperoleh data melalui kepustakaan kemudian dianalisis dan dikombinasikan. Dengan demikian hasil dari lapangan dan hasil dari kepustakaan ditemukan suatu pemikiran yang sesuai antara pemikiran Beverly dan pelaksanaan Misi Umat Pasionis. Hasil dari cetusan pemikiran Beverly dan Misi Umat Pasionis menjadi sarana untuk evaluasi dan melihat misi ini secara komprehensif dan holistik. Maka dari itu, spiritualitas pasionis terus menerus membaharui diri dengan ilmu, peneletian, riset yang mumpuni tentang suatu pewartaan atau misi. Misi Umat Pasionis menjadi sumbu dan obor yang baik dalam kesaksian pewartaan misi Gereja di dunia. Misi ini tidak berhenti pada selesainya acara melainkan terus berlangsung dan dihidupi umat beriman.